Green jobs and women workers: employment, equity, equality. Draft report (Brussels, 2009)
"Achieving sustainability depends on equal attention to economic, environmental and social factors and their integration through sustainable development strategies. Green economy initiatives which aim at creating more environmentally-sound economies may not fully incorporate fundamental social requirements such as income equity, job quality and gender equality. If they do not take account of these social factors, they may maintain or even aggravate the negative social and distributive trends of the traditional economy including existing inequalities and gender gaps."